Film Translation - Fook Khoon Wong (Journal of Modern Languages)
This paper seeks to examine two current forms of film translating; dubbing and subtitling. The paper compares these forms together, and come up with some tentative conclusions. It also indicates that dubbing and subtitling by virtue of their importance and apparent necessity to one of the modern forms of art, that is, film production, can no longer be left to a vague existence. Rather, as two very specialized modes of translation, they should be given their due share of attention.